Do CEO Cultural Traits Shape Corporate Tax Aggressiveness? Quantile Regression Evidence from US Firms - Ayadi, Jihen; Khlif, Hichem (Journal of Cultural Analysis and Social Change, 2026)
This study investigates the influence of CEO cultural characteristics on the strategic tax decisions on 90 U.S non-financial S&P 500 firms over the years 2014 to 2017. Such traits are ranked by their demographic characteristics (age, gender, ethnic), professional attributes (education, degree, tenure, experience, CEO duality, founder, compensation), social interactions (marital, military, political ) and behavioral habits (overconfidence), As cultural imprint of the executive, it indicates the directs impact of executive culture on the corporate tax aggressiveness measured as TA = (1 – ETR). Drawing on upper echelon’s theory, agency, prospect, positive accounting, executive power, CSR/legitimacy, and cognitive bias theories, the analyze illustrates its point., through a quantile regression. The results show that demographic and social traits, such as older age, female gender, marital status, and military background, are associated to less tax aggressiveness, especially at lower quantiles. On the other hand, professional and behavioral characteristics that depict the financial education, longer tenure, CEO duality, higher compensation incentives, and overconfidence greatly enhance tax aggressiveness with the impact becoming more pronounced at the higher quantiles. This study adds to the extant literature a further understanding of the importance of CEO cultural imprints in shaping corporate tax strategies, providing valuable input for boards, investors, and regulators balancing tax optimization with issues of compliance and reputation.